二齿差摆线针轮行星传动中摆线轮等效代换齿廓的研究 - 马英驹 (Jixie chuandong)
a theory of equivalently substituting the tooth profife of cycloidal gear in twoteeth difference cycloid gearing, by using equidistant curve of curtate epicycloid as toothprofile cycloidal gear is presented mathematical models, calculation methods and practicalexamples for obtaining parameters of equivalent profile are also provided. By this meansthe cusp of tooth profile of cycloidal gear areeliminatd but function of transfer motion areinvariant.